The dried blood spot sampling method in the laboratory medicine - Laštovičková, Lenka; Kanďár, Roman (Univerzita Komenského v Bratislave, 2019)
The minimization is currently expanding in all fields of human life. The smaller size of analytical instruments and their higher sensitivity enables an analysis of small amounts of a biological material with a very low consumption of chemicals, what is economically and also environmentally beneficial. A patient friendly and minimal invasive sample collection is therefore more than required. The dried blood spot (DBS) sampling standardly used in the newborn screening (NS) may be an option. The sample collection is simple, non-invasive, does not require trained medical personnel assistance and also storing and transportation of these samples is much easier in comparison with the whole blood samples. The DBS sampling method is used in the therapeutic drug monitoring or in the diagnosis of infectious diseases and its usage is still spreading. In some cases, it is still only a research object, but it shows a big potential for a future use. It could completely replace the whole venous blood collection in some cases, for example in the metabolic screening of diabetic patients or monitoring of treatment response, and it can overall simplify the sample collection and the transportation process (Tab. 1, Ref. 152).
Metoda suché kapky krve při odběru vzorku v laboratorní medicíně
Keywords: dried blood spot; sample collection; laboratory medicine; suchá kapka krve; odběr vzorku; laboratorní medicína